1994
DOI: 10.1103/physrevc.50.1456
|View full text |Cite
|
Sign up to set email alerts
|

Theory of parity violation in compound nuclear states: One particle aspects

Abstract: In this work we formulate the reaction theory of parity violation in compound nuclear states using Feshbach s projection operator formalism. We derive in this framework a complete set of terms that contribute to the longitudinal asymmetry measured in experiments with polarized epithermal neutrons. We also discuss the parity violating spreading width resulting from this formalism. We then use the above formalism to derive expressions which hold in the case when the doorway state approximation is introduced. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, all ten measured asymmetries for resonances below 250 eV had the same sign. Models proposed to explain this sign effect are based on either distant [38,39,40,41,42,43,44,45,46] or nearby [47,48,49,50,51,52,53] (parity) doorway states. Perhaps the same type of model could be invoked to explain the observed deviations in the neutron width distributions from the expected PT shape, while at the same time these deviations might provide some clue to the physical origins of the doorway.…”
Section: Discussionmentioning
confidence: 99%
“…However, all ten measured asymmetries for resonances below 250 eV had the same sign. Models proposed to explain this sign effect are based on either distant [38,39,40,41,42,43,44,45,46] or nearby [47,48,49,50,51,52,53] (parity) doorway states. Perhaps the same type of model could be invoked to explain the observed deviations in the neutron width distributions from the expected PT shape, while at the same time these deviations might provide some clue to the physical origins of the doorway.…”
Section: Discussionmentioning
confidence: 99%
“…There are also other explanations of the permanent sign effect in 232 Th. The contributions from Distant doorway states [60,[73][74][75][76] appear to be too small. The neutron PV potential scattering contribution [70,109], as well the contributions calculated using optical potentials [71,110,111], also seem to be too small.…”
Section: Comments About Other Mechanisms Of the Permanent Sign Pv And...mentioning
confidence: 87%
“…Several papers [60,[70][71][72][73][74][75][76] described in the review [9] suggested mixing of the doorway states of opposite parity as a source of the permanent sign effect in 233 Th. For example, in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the same size matrix element was used the average asymmetry was almost two orders of magnitude smaller than measured. Recently more extensive theoretical investigations characterized several terms that could contribute to PNC asymmetries in the CN [8,9]. Additional terms were derived and evaluated.…”
mentioning
confidence: 99%
“…We will refer to these resonances as p 1/2 . The leading term of the asymmetry P can be written [6,9] P (E r ) = −2…”
mentioning
confidence: 99%